Selective Inactivation of p53 Facilitates Mouse Epithelial Tumor Progression without Chromosomal Instability - Lu, Xiangdong (American Society for Microbiology, 2001)
We examined the selective pressure for, and the impact of, p53 inactivation during epithelial tumor evolution in a transgenic brain tumor model. In TgT(121) mice, cell-specific inactivation of the pRb pathway in brain choroid plexus epithelium initiates tumorigenesis and induces p53-dependent apoptosis. We previously showed that p53 deficiency accelerates tumor growth due to diminished apoptosis. Here we show that in a p53(+/−) background, slow-growing dysplastic tissue undergoes clonal progression to solid angiogenic tumors in all animals. p53 is inactivated in all progressed tumors, with loss of the wild-type allele occurring in 90% of tumors. Moreover, similar progression occurs in 38% of TgT(121)p53(+/+) mice, also with loss of at least one p53 allele and inactivation of p53. Thus, the selective pressure for p53 inactivation, likely based on its apoptotic function, is high. Yet, in all cases, p53 inactivation correlates with progression beyond apoptosis reduction, from dysplasia to solid vascularized tumors. Hence, p53 suppresses tumor progression in this tissue by multiple mechanisms. Previous studies of fibroblasts and hematopoietic cells show that p53 deficiency can be associated with chromosomal instability, a mechanism that may drive tumor progression. To determine whether genomic gains or losses are present in tumors that progress in the absence of p53, we performed comparative genomic hybridization analysis. Surprisingly, the only detectable chromosomal imbalance was partial or complete loss of chromosome 11, which harbors the p53 gene and is thus the selected event. Flow cytometry confirmed that the majority of tumor cells were diploid. These studies indicate that loss of p53 function is frequent under natural selective pressures and furthermore that p53 loss can facilitate epithelial tumor progression by a mechanism in addition to apoptosis reduction and distinct from chromosomal instability.